Poly(ethylene glycol)-co-methacrylamide-co-acrylic acid based nanogels for delivery of doxorubicin. Issue 14 (21st September 2016) - Kumar, Parveen; Behl, Gautam; Sikka, Manisha; Chhikara, Aruna; Chopra, Madhu
Abstract: Polymeric nanogels have been widely explored for their potential application as delivery carriers for cancer therapeutics. The ability of nanogels to encapsulate therapeutics by simple diffusion mechanism and the ease of their fabrication to impart target specificity in addition to their ability to get internalized into target cells make them good candidates for drug delivery. The present study aims to investigate the applicability of poly(ethylene glycol)- co -methacrylamide- co -acrylic acid (PMA)-based nanogels as a viable option for the delivery of doxorubicin (DOX). The nanogels were synthesized by free radical polymerization in an inverse mini-emulsion and characterized by nuclear magnetic resonance spectroscopy ( 1 H NMR), Fourier transform infrared spectroscopy, dynamic light scattering, transmission electron microscopy (TEM), X-ray diffraction and differential scanning calorimetry. DOX was physically incorporated into the nanogels (PMA-DOX) and the mechanism of its in vitro release was studied. TEM experiment revealed spherical morphology of nanogels and the hydrodynamic diameter of the neat nanogels was in the range of 160 ± 46.95 nm. The size of the nanogels increased from 235.1 ± 28.46 to 403.7 ± 89.89 nm with the increase in drug loading capacity from 4.68 ± 0.03 to 13.71 ± 0.01%. The sustained release of DOX was observed upto 80 h and the release rate decreased with increased loading capacity following anomalous release mechanism as indicated by the value of diffusion exponent ( n = 0.64–0.75) obtained from Korsmeyer–Peppas equation. Further, cytotoxicity evaluation of PMA-DOX nanogels on HeLa cells resulted in relatively higher efficacy (IC50 5.88 μg/mL) as compared to free DOX (IC50 7.24 μg/mL) thus demonstrating that the preparation is potentially a promising drug delivery carrier.